2018
DOI: 10.1097/inf.0000000000001712
|View full text |Cite
|
Sign up to set email alerts
|

A Double-blind, Randomized, Placebo-controlled Trial of Lactobacillus acidophilus for the Treatment of Acute Watery Diarrhea in Vietnamese Children

Abstract: This was a large double-blind, placebo-controlled trial in which the probiotic underwent longitudinal quality control. We found under these conditions that L. acidophilus was not beneficial in treating children with acute watery diarrhea.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
20
0
2

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(22 citation statements)
references
References 27 publications
0
20
0
2
Order By: Relevance
“…Furthermore, our yogurt contained LF and also lactic bacteria. Habitual yogurt consumption and food intake, including lactic bacteria, have been reported to alleviate gastrointestinal symptoms [30][31][32][33][34][35]. Yogurt containing lactic bacteria without LF might affect intestinal microbiota composition.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, our yogurt contained LF and also lactic bacteria. Habitual yogurt consumption and food intake, including lactic bacteria, have been reported to alleviate gastrointestinal symptoms [30][31][32][33][34][35]. Yogurt containing lactic bacteria without LF might affect intestinal microbiota composition.…”
Section: Discussionmentioning
confidence: 99%
“…A study by Sur et al [5] involving children aged 1–5 years in an urban slum in India found that probiotics could help to prevent acute diarrhea. In addition, in an RCT conducted in Vietnam by Hong Chau et al [8], the time to the disappearance of diarrhea was shorter, albeit not significantly, in the group administered probiotics. On the other hand, Hatakka et al [15] found no association between lactobacillus rhamnosus consumption and respiratory infection in children attending daycare centers in Finland.…”
Section: Discussionmentioning
confidence: 99%
“…In a study in Finland of 40 patients with diarrhea, compared with placebo, Lactobacillus reuteri was associated with a smaller proportion of symptomatic patients on day 2 (26% vs 81%, p = 0.0005) and short treatment duration (1.7 days vs 2.9 days, p = 0.07) [7]. However, several randomized controlled trials (RCTs) showed that the frequency of diarrhea was slightly, but not significantly, lower in probiotic groups than in placebo groups [8–10]. As part of a cohort analysis of elderly individuals with proximal femur fractures, Mallina et al [11] reported no preventive effect of a probiotic against Clostridium difficile -associated diarrhea.…”
Section: Introductionmentioning
confidence: 99%
“…When reported, the standard deviation (SD) was utilized or computed from the median and interquartile range (IQR). In four trials reporting median and IQR [ 10 , 11 , 16 , 17 ], missing means and SDs were estimated using the formula recommended by Wan et al [ 18 ] and McGrath et al [ 19 ].…”
Section: Methodsmentioning
confidence: 99%
“…However, in the light of recent null studies, there is still controversy as to whether the efficacy of Lactobacillus acidophilus has been established. A relatively large, prospective randomized controlled trial (RCT) carried out in Vietnam, including 290 children aged 11.8 months to 21.5 months, compared the operation of Lactobacillus acidophilus , at a dose of 4 × 10 8 CFU twice daily, to a matching placebo, found no differences in outcomes, including duration of diarrhea and stool frequency in the first three days after enrollment, between groups [ 10 ]. Moreover, in several additional randomized controlled trials (RCTs), no difference in diarrhea duration was reported across groups [ 11 , 12 ].…”
Section: Introductionmentioning
confidence: 99%